Strategi Pembelajaran pada Diklat Analis Pertahanan Negara dalam Menghadapi Tantangan Integrasi Nasional - Zakaria; R. Okta Kurniawan (Badan Pendidikan dan Pelatihan Kementerian Pertahanan, 2025)
The importance of forming an effective learning strategy in National Defense Analyst education and training is becoming increasingly relevant in the context of national integration. Education plays a role as a tool to strengthen the sense of nationality and unity in cultural, religious, and ethnic diversity. In facing these challenges, an effective learning strategy must be able to instill national values, introduce diversity as a national wealth, and facilitate intercultural dialogue. A learning approach that focuses on collaboration, intercultural understanding, and national character development is needed to form a society that is not only academically intelligent, but also tolerant and respectful of each other. Therefore, educators need to develop methods that integrate national integration values into every aspect of learning, both in the curriculum, extracurricular activities, and daily interactions in the educational environment. This study aims to explore the right learning strategy to face the challenges of national integration through national defense analysis training. The method used in this study is a qualitative approach with descriptive analysis. Data were collected through literature studies, questionnaires, and observations of the implementation of training in defense education institutions. The results of the study indicate that the use of problem-solving and collaborative learning strategies is an important factor in forming a more comprehensive understanding and attitude of training participants towards issues of national defense and national integration. Interactive learning based on simulations or real case studies can hone the analytical and strategic skills of participants, so that they can make a positive contribution to achieving harmonious national integration. Andi t will have an impact on changes to the National Defense Analyst training curriculum, monitoring and evaluating the implementation of attitude-based and collaboration learning strategies.